2022
DOI: 10.3390/cryst12070924
|View full text |Cite
|
Sign up to set email alerts
|

Board Level Drop Test for Evaluating the Reliability of High-Strength Sn–Bi Composite Solder Pastes with Thermosetting Epoxy

Abstract: The Sn–Bi solder paste is commonly used in electronic assembly and packaging, but its brittleness causes poor reliability in shock environments. In this study, the mechanical reliability of Sn–Bi solder paste and Sn–Bi composite solder paste with thermosetting epoxy (TSEP Sn–Bi) was investigated with the board level drop test. The crack characterizations of solder joints were evaluated using a stereomicroscope after the dye and pull test. The microstructure characterization and failure types of solder joints w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The research result indicated that the appropriate addition of epoxy resin could notably improve the spreadability and shear properties of Sn-Bi solder pastes. Moreover, the thermal reliability and drop characteristics of Sn-Bi epoxy solder joints were enhanced, which could mainly benefit from the mechanical refinement of epoxy resin [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research result indicated that the appropriate addition of epoxy resin could notably improve the spreadability and shear properties of Sn-Bi solder pastes. Moreover, the thermal reliability and drop characteristics of Sn-Bi epoxy solder joints were enhanced, which could mainly benefit from the mechanical refinement of epoxy resin [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%